Literature Review Pengaruh Lingkungan Kerja, Disiplin Kerja dan Komunikasi terhadap Karyawan CV. Tidar Jaya - Fathia Rizqi Ananda (Penerbit Goodwood, 2023)
Purpose: This study aimed to determine the performance of CV. Tidar Jaya what kind of employee performance occurs during work Constraints in the work discipline that occur in this company that cause this research to take place in a less optimal work discipline make it less able to do a job that is undertaken. In this study, we also examined the communication system and work environment; however, for these variables, everything was significant. Methodology: A literature review using the Google Scholar tool was conducted and summarized in this study. In addition to the literature review, it also used references from various written data sources. Mendley and Google Scholar were widely used to write this article. Results: The results of this study indicate that discipline is not significant for employee performance in CV. Tidar Jaya. However, in a communication system, work environment variables are significant. means that discipline becomes an obstacle in this research but is not too serious. Limitations: This literature review explains the role of work environment, discipline, and work communication on employee performance. Contribution: This research can contribute to readers and anyone who wants to conduct research on work environment, discipline, and communication on employee performance. If someone wants to conduct the research and read what happened in this research, they can better conclude what they should make.